Between resistance and co-operation; Contact zones in the Aru Islands in the VOC period - Hägerdal, Hans (UI Scholars Hub, 2019)
The article is focused on early colonial interaction with the Aru Islands, geographically located in southern Maluku, at the easternmost end of the Indian Ocean world. The study examines how relationships were constructed in the course of the seventeenth century, how they were institutionalized and how this engendered forms of hybridity. Moreover, it discusses forms of resistance and avoidance in relation to the Dutch East India Company (VOC). Aru constitutes an interesting case as it is was one of the easternmost places in the world in which Islam and Christianity gained a (limited) foothold in the early-modern period, and it also marked the outer limit of Dutch authority. Aru differed from most geographical areas approached by the VOC because of its lack of any large-scale political structures and its relatively non-hierarchical society. The article discusses the forging of Dutch-Arunese political ties after the Banda massacre in 1621, as well as the role of Asian competitors of the VOC such as the Makassarese and Ceramese, the increasing adaptation to world religions in an Arunese setting, conditions in the European-indigenous contact zones and, finally, the conflicts arising from the imbalances between western and eastern Aru, in which the VOC repeatedly intervened to suppress the villages of the Backshore (east coast).